2022
DOI: 10.1177/0160323x221089661
|View full text |Cite
|
Sign up to set email alerts
|

Local Autonomy and Response to the COVID-19 Pandemic

Abstract: We examine local government response to the COVID-19 pandemic in the United States utilizing a unique dataset created by the National League of Cities. The most common action by local governments was changing administrative procedures and implementing policies aimed at prevention or “flattening the curve”. The general public was the most common population target. In addition to detailing the most common local action types, policy areas, and population targets, we analyze local response based on the autonomy gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Like Juneau, these entities combine city and county government, increasing coordination. Further evidence for our claim that home rule was not decisive comes from the finding looking at data across the U.S. that there was no meaningful correlation between home rule and the rate of COVID-19 local actions ( Patton et al 2022 ). Similarly, another study found no relationship between home rule and premature mortality, though it did support our argument that county government structure mattered in public health outcomes ( Costich and Patton 2012 ).…”
Section: Alternative Explanationsmentioning
confidence: 95%
“…Like Juneau, these entities combine city and county government, increasing coordination. Further evidence for our claim that home rule was not decisive comes from the finding looking at data across the U.S. that there was no meaningful correlation between home rule and the rate of COVID-19 local actions ( Patton et al 2022 ). Similarly, another study found no relationship between home rule and premature mortality, though it did support our argument that county government structure mattered in public health outcomes ( Costich and Patton 2012 ).…”
Section: Alternative Explanationsmentioning
confidence: 95%
“…Birkland et al (2020) noted that state partisanship drove fragmented response to the COVID pandemic, defining state public health interventions with varying outcomes. Patton et al (2022) examined local governments' response to the COVID‐19 pandemic in the United States using a unique dataset created by the National League of Cities. The study found that the most common action by local governments was changing administrative procedures and implementing policies aimed at prevention or “flattening the curve.” The general public was the most common population target.…”
Section: Introductionmentioning
confidence: 99%
“…Strano (2020) and McDonald III et al (2020) have also highlighted similar issues in their works, emphasizing local governments' need for greater autonomy during crises. Drawing from Patton et al (2022), this study delves deeper into the complexities of local government response to the COVID‐19 pandemic, particularly in the context of the autonomy granted by states to local governments.…”
Section: Introductionmentioning
confidence: 99%